Origanum compactum essential oil as a green inhibitor for mild steel in 1 M hydrochloric acid solution: Experimental and Monte Carlo simulation studies. (2021) - Lazrak, J.; El Assiri, El H.; Arrousse, N.; El-Hajjaji, F.; Taleb, M.; Rais, Z.; Farah, A.; Ramzi, A.; Hammouti, B.
Abstract: The chemical composition of origanum compactum essential oil (OCEO) was performed by gas-chromatography (GC) and gas chromatography–mass spectrometry (GC–MS). The essential oil was predominated by thymol (28.36%), carvacrol (25.44%), γ-terpinene (18.39%) and p-Cymene (11.21%). The corrosion-resistance ability of mild steel in hydrochloric acid solution using OCEO was tested by means of mass loss measurements, electrochemical and Monte Carlo simulations (MCS). The experimental results indicated that OCEO acted as an efficient inhibitor against the mild steel corrosion in 1 M HCl, and its inhibition efficiency increased with increasing concentration of the essential oil to attain 90% at 1 g.L −1 . The adsorption of this essential oil on a mild steel surface follows Temkin's adsorption isotherm and involved a physisorption mode. While, polarization studies showed that origanum compactum essential oil behaves as a mixed type inhibitor. Furthermore, MCS were carried out to assert the experimental results by exploring the configurational adsorption behavior of OCEO on the metal surface.